(untitled) (Journal of Imam Al-Kadhim College, 2023)
The rule of denying the path is one of the important legal rules in Islamic jurisprudence. Jurists have relied on this rule in many legal rulings. The rule states that every action leads to the authority of infidels are denied, as Islamic law does not leave room for non-Muslims to control and dominate Muslims in any field. From the areas of individual or social life, and I considered this to be forbidden for Muslims to do under any heading, any contract, agreement, and any transaction, arrangement, or contract that results in the infidels prevailing over the believers has no legal legitimacy. The rule of denying the path, as a jurisprudential principle, has a fixed role and influence on the behavior of the Islamic system, its decisions, and its policies. This principle has a very important place in the external relations of the Islamic State with foreigners. Denying the injustice and oppression to which Muslims are exposed, preserving independence and denying dependence on foreigners is the basis of this rule and constitutes the basic structure guaranteeing the independence of society and preventing domination.